ANTHROPOMORPHIC IMAGES ON POTTERY OF THE SAMOSDELKA SETTLEMENT - Zilivinskaa, Emma Davidovna; Boldyreva, Ekaterina Mihajlovna; Vasil'ev, Dmitrij Viktorovic (History, Archeology and Ethnography of the Caucasus, 2023)
The Samosdelka fortified settlement, located in the center of the Volga delta, dates back to the 9th – the first half of the 14th century. The study aims to introduce anthropomorphic images on unglazed and glazed vessels found during excavations of this site. On crude molded vessels, which can be associated with the nomadic component of the population of the Lower Volga region of the 9th–12th centuries, images of anthropomorphic figures are observed on wet clay. The figures have large round heads, which in some cases have facial features. The torso, arms and legs are mostly not visible. Similar images are known in the pottery of the Saltovo-Mayaki culture and the “nomadic” pottery of Sarkel. They might have had a sacred meaning. Anthropomorphic images on imported glazed ceramics are associated with the Islamic art. Parts of the human body imagery are found on both kashin and red clay pottery. Two kashin vessels depict scenes from secular life, a musician playing a stringed instrument, and a ruler on a throne. Here the images of people are of decorative nature. At the same time, pottery with mascarons could have had a cult-magical function, as well as a platter depicting a mythical bird-woman, a siren. The paper analyzes the images and compares them with a wide range of analogies published both in Russian and foreign publications. The methodological basis of archaeological and cultural research is historical comparative studies, in particular, comparative-historical and comparative-typological methods. On the example of the anthropomorphic images of the Samosdelka fortified settlement, one can see how, over time, their sacred functions become less pronounced, and the depictions take on the form of decoration.
Keywords: Lower Volga region; Middle Ages; anthropomorphic images; molded pottery; nomads; Saltovo-Mayaki culture; glazed pottery; Muslim East; sacred meaning